An Unpropitious Surprise Post Vaginal Hysterectomy – A Case of Incidentally Discovered Extra-Gastrointestinal Stromal Tumour - Minal, Jessica; P V, Nikhil; Nagabhushan, Bhargavi Kalburgi; Murali, Nirupama; Gaffoor, Nidha (International Journal of Human and Health Sciences (IJHHS), 2024)
Extra-gastrointestinal stromal tumours (EGIST) are rare mesenchymal tumours that arise outside the gastrointestinal tract and mainly affect the omentum, mesentery, and retroperitoneum. We report a case of EGIST in an elderly female patient at an unusual location. The patient was referred to our centre with hemoperitoneum post vaginal hysterectomy for the treatment of third-degree utero-vaginal prolapse. Ultrasonography (USG) of abdomen and pelvis was done which revealed a heterogenous tumour in the upper abdomen. The tumour mass measured 23x18x8.5cms and was abutting the greater curvature of stomach without infiltration. A diagnosis of extra-gastrointestinal stromal tumour, spindle cell type, high grade, with pseudo signet ring appearance was rendered based on the morphology and immunohistochemistry with CD117(c-kit) and DOG1. Rupture of cancerous mass in the abdomen is one of the causes to be kept in mind in hemoperitoneum and EGIST should be considered in the differential diagnosis of large, multi-nodular, primary lesions of the abdomen. A high degree of suspicion is needed as these patients present late and are often diagnosed incidentally during investigations for unrelated medical conditions. 10% of EGISTs are primarily disseminated and the site of origin cannot be established with certainty, emphasizing the enigma of its origin as encountered in the present case. International Journal of Human and Health Sciences Vol. 08 No. 02 Apr’24 Page: 207-211